Actinomycosis Calcaneum- A Rare Case Report - Vipin Sharma; Abhimanyu Virmani; Manik Sehgal; Ravi K Soni; Seema Sharma (Journal of Clinical and Diagnostic Research, 2017)
Actinomyces is anaerobic, gram-positive bacilli that superficially resemble fungi and give rise to suppurative and granulomatous infection. The organisms are commensals to human body but under suitable conditions can involve any organ system. Cervicofacial actinomycosis is the most common presentation while actinomycosis of extremity especially calcaneum is very rare. We report a rare case of 40-year-old woman who presented with chief complaints of pain and swelling of the right foot for one year. She was diagnosed with isolated calcaneal actinomycosis and was managed by antibiotics, curettage of calcaneum and triple arthrodesis.